Mechano-immunology in microgravity - Murali, Anirudh; Sarkar, Ram Rup (Life Sciences in Space Research, 2023)
Life on Earth has evolved to thrive in the Earth's natural gravitational field; however, as space technology advances, we must revisit and investigate the effects of unnatural conditions on human health, such as gravitational change. Studies have shown that microgravity has a negative impact on various systemic parts of humans, with the effects being more severe in the human immune system. Increasing costs, limited experimental time, and sample handling issues hampered our understanding of this field. To address the existing knowledge gap and provide confidence in modelling the phenomena, in this review, we highlight experimental works in mechanoimmunology under microgravity and different computational modelling approaches that can be used to address the existing problems.
Keywords: Computational modelling; Immune system; Mechano-immunology; Mechanotransduction; Microgravity

Dynamic cellular responses to gravitational forces: exploring the impact on white blood cell(s) - Murali, Anirudh; Sarkar, Ram Rup (Biomicrofluidics, 2024)
In recent years, the allure of space exploration and human spaceflight has surged, yet the effects of microgravity on the human body remain a significant concern. Immune and red blood cells rely on hematic or lymphatic streams as their primary means of transportation, posing notable challenges under microgravity conditions. This study sheds light on the intricate dynamics of cell behavior when suspended in bio-fluid under varying gravitational forces. Utilizing the dissipative particle dynamics approach, blood and white blood cells were modeled, with gravity applied as an external force along the vertical axis, ranging from 0 to 2 g in parameter sweeps. The results revealed discernible alterations in the cell shape and spatial alignment in response to gravity, quantified through metrics such as elongation and deformation indices, pitch angle, and normalized center of mass. Statistical analysis using the Mann-Whitney U test underscored clear distinctions between microgravity (<1 g) and hypergravity (>1 g) samples compared to normal gravity (1 g). Furthermore, the examination of forces exerted on the solid, including drag, shear stress, and solid forces, unveiled a reduction in the magnitude as the gravitational force increased. Additional analysis through dimensionless numbers unveiled the dominance of capillary and gravitational forces, which impacted cell velocity, leading to closer proximity to the wall and heightened viscous interaction with surrounding fluid particles. These interactions prompted shape alterations and reduced white blood cell area while increasing red blood cells. This study represents an effort in comprehending the effects of gravity on blood cells, offering insights into the intricate interplay between cellular dynamics and gravitational forces.

Impact of gravitational forces on Red Blood Cell dynamics in biofluid suspension - Murali, Anirudh; Sarkar, Ram Rup (Life Sciences in Space Research, 2025)
The growing interest in space exploration and human spaceflight has highlighted the critical challenges posed by microgravity on human physiology. Among these, a significant issue is space anemia, which adversely affects Red Blood Cells (RBC) and alters its behavior. RBC depends on biofluids, for their systemic transport, a process that experiences disruption in the microgravity environment. This study aims to quantitatively address the puzzle of how red blood cells are influenced by gravity when they are suspended in bio-fluid. Dissipative Particle Dynamics (DPD) approach was used to model blood and the cell by applying gravity as an external force along the vertical axis and varied from 0g to 2g during parameter sweeps. Key metrics, including Elongation and Deformation indices, pitch angle, and normalized center of mass, were utilized to assess cellular behavior. Results revealed that gravity induces shape changes and spatial alignment in red blood cells. The Elongation Index and the normalized center of mass declined linearly with the applied gravity. Correlation analysis showed a strong correlation between applied gravity and the aforementioned variables. Additionally, forces acting on the cell, such as drag, shear stress, and solid forces, diminished as gravitational force increased. Further analysis indicates that increasing gravity affected the cell's velocity, resulting in prolonged proximity to vessel walls and intensified viscous interactions with surrounding fluid particles, thereby triggering morphological changes. This study provides crucial insights into the biophysical effects of gravity on the red blood cell and presents a significant step toward understanding cellular dynamics under altered gravitational conditions.
Keywords: Altered gravity; Computational modeling; Dissipative Particle dynamics; Fluid flow; Red Blood Cell